Determinan Intellectual Capital Disclosure Pada Perusahaan LQ45 Yang Terdaftar di BEI - Desy Lusiana Situmorang; Aji Sukarno; Joko Utomo; Budi Santosa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The purpose of this study was to determine the effect of managerial ownership, institutional ownership, foreign ownership, government ownership, profitability, and leverage on intellectual capital disclosure. The population in this study is LQ45 companies listed on the Indonesia Stock Exchange in 2016-2018. The method used in this study is purposive sampling, with the following criteria: 1) Companies listed on the LQ45 Index throughout 2016-2018 on the Indonesia Stock Exchange (IDX). 2) Companies that were successively registered in the LQ45 Index throughout 2016-2018 3) Companies that published annual reports in a row during 2016-2018 as of April 31, 2019. The sample used was secondary data from Indonesia Stock Exchange (IDX), which is an annual report of 75 companies. The analysis technique used is multiple linear regression. The results showed that government ownership, profitability and leverage had a positive effect on intellectual capital disclosure. While managerial ownership, institutional ownership and foreign ownership have no effect on intellectual capital disclosure.